Psychology And Literature: An Analysis Of The Reciprocity - Kashyap Bishwas (Elementary Education Online, 2023)
It goes both ways in the relationship between psychology and literature. Literature is created by human souls, and human souls are fed by literature. Human psychical receptions evaluate human and natural life viewpoints and present examples of literal works; on the other hand, literature likewise considers life's facts to make obvious human soul perspectives. Students in these courses are exposed to various points of view and connections across disciplines outside of literature. A possible one of them is comparative literature. A rich environment for the growth of an observant, well-rounded reader, writer, and thinker is provided by aiming to gain insights into literature and culture in a comparative perspective. Students can learn to analyze and evaluate literary and cultural works from other sources and in languages other than their own through comparative literature. We receive instruction in presenting compelling arguments, mastering and applying various theoretical and methodological methods, and conversing with academics from the disciplines of Comparative Literature and other modern and ancient languages.